Intratumoral heterogeneity drives acquired therapy resistance in a patient with metastatic prostate cancer - Dena P. Rhinehart; Jiaying Lai; David E. Sanin; Varsha Vakkala; Adrianna Mendes; Christopher Bailey; Emmanuel S. Antonarakis; Channing J. Paller; Xiaojun Wu; Tamara L. Lotan; Rachel Karchin; Laura A. Sena (npj Precision Oncology)
Abstract Metastatic prostate cancer (PCa) is not curable due to its ability to acquire therapy resistance. Theoretically, acquired therapy resistance can be driven by changes to previously sensitive cancer cells or their environment and/or by outgrowth of a subpopulation of cancer cells with primary resistance. Direct demonstration of the latter mechanism in patients with PCa is lacking. Here we present a case report as proof-of-principle that outgrowth of a subpopulation of cancer cells lacking the genomic target and present prior to therapy initiation can drive acquired resistance to targeted therapy and threaten survival in patients with PCa.